2019
DOI: 10.1590/s0004-2803.201900000-69
|View full text |Cite
|
Sign up to set email alerts
|

METALLOTHIONEIN-2A (RS1610216&RS28366003) GENE POLYMORPHISMS AND THE RISK OF STOMACH ADENOCARCINOMA

Abstract: BACKGROUND: Gastric cancer is the fourth most common cause of worldwide cancer. Also in contrast to the huge advances in curing, the chance of living is very low even in surgery cases. Having a genetic predisposition plays an important role in cancer development. The association between Metallothionein-2A gene polymorphisms and the risk of adenocarcinoma has been widely studied, yet there is only one study on stomach diseases. OBJECTIVE: In this study, we aimed to investigate the association between 2 (MT-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…found that, compared with individuals with the AA genotype at rs28366003, individuals with the GG genotype had a significantly increased risk of gastric cancer, based on 95 patients with gastric cancer and 90 healthy individuals in Iran. 10 In the current pooled analysis, we confirmed that MT2A rs28366003 was associated with the risk of cancer, including breast cancer and prostate cancer. Furthermore, we observed this association of rs28366003 and cancer risk in both Asian and Caucasian subpopulations.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…found that, compared with individuals with the AA genotype at rs28366003, individuals with the GG genotype had a significantly increased risk of gastric cancer, based on 95 patients with gastric cancer and 90 healthy individuals in Iran. 10 In the current pooled analysis, we confirmed that MT2A rs28366003 was associated with the risk of cancer, including breast cancer and prostate cancer. Furthermore, we observed this association of rs28366003 and cancer risk in both Asian and Caucasian subpopulations.…”
Section: Discussionsupporting
confidence: 74%
“…Sensitivity analysis for rs28366003 showed that no individual study significantly changed the pooled ORs. However, sensitivity analysis for rs1610216 showed a significant change in the pooled ORs after the study of Shokrzadeh et al 10 was removed (Figure 3). Potential publication bias was evaluated by two test methods TSA showed that sample size was insufficient to obtain a significant result; thus, more studies are required ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations